Bose-Einstein correlations in various collision systems and energies measured with the CMS experiment - Padula, Sandra S. [UNESP] (My University, 2015)
Two-particle, quantum-statistical (Bose-Einstein) correlations are measured with the CMS experiment in pp collisions at 0.9, 2.76 and 7 TeV center-of-mass energies, as well as in pPb and peripheral PbPb collisions, respectively at 5.02 and 2.76 TeV center-of-mass energy per nucleon. The analysis is performed as a function of both the charged particle multiplicity and the average transverse pair momentum. The measurement is performed with charged particles and the full available statistics in pp collisions, being also compared to previous one-dimensional results from CMS. The analysis is then extended to two- and three-dimensions for investigating the source lengths of homogeneity in different spatial directions. Furthermore, low pT pions and kaons, which are identified from their energy loss in the silicon tracker, are used to further extend the measurements to pp, pPb and PbPb systems at the available energies. Radius fit parameters on the order of 1-5 fm are found, the largest values corresponding to very high multiplicity pPb interactions and for similar multiplicity PbPb collisions.